Evaluation of the “antidotal” potential of mangifera indica L. leaves extract on sodium arsenate exposed male wistar rats using some biochemical markers (2017)
Abstract: In order to evaluate the antidotal potential of Mangifera indica L leaves extract on sodium arsenate exposed male Wistar rats using some biochemical markers, forty-two apparently healthy male Wistar rats (weight range 120-160 g) were used in the study. The animals were randomly separated into six groups. Other than groups “A” (non-exposed control) and “B” (exposed control), groups; C, D, E, and F respectively were treated with different dosages of Mangifera indica L extract viz., l00 mg/kg and 200 mg/kg extract. Volumes of extract administered did not exceed 0.2 ml regardless of the body weight of the animal respectively. Some biochemical parameters assessed were: serum protein, albumin, conjugated bilirubin, unconjugated bilirubin (ICB), aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP),gamma-glutamyl transferase (GGT), urea, creatinine, creatine kinase (CK), lactate dehydrogenase (LDH),acid phosphatase, prostatic phosphatase, serum lipid profile, that is total cholesterol, low density lipoprotein cholesterol (LDL), high density lipoprotein cholesterol (HDL), and the hormones, testosterone and luteinizing hormone levels. Group “B” had significantly (P<0.05) higher activities for AST, GGT, CK, LDH and higher cholesterol concentration when compared to Mangifera indica treated groups and to the non-exposed control. Testosterone and LH were significantly (P<0.05) lower in group “B” unlike the Mangifera indica treated groups and group “A”. This observation could be attributed to adverse effect of toxicosis on exposure to animals in group “B”. Antitodal property of the extract, due to one or more of its phytochemicals such as flavonoids, tannins alkaloid and anthraqunones could be the most probable reason for potential therapeutic potential. Conclusively, this observation gives credence to its cytoprotective and antitodal properties.